Measurement of public health impacts of cannabis legalization in Canada to reflect policy maker priorities: A rapid scoping review of instruments and content domains. (1st July 2022) - Lazor, Tanya; Blondal, Erik; Scheim, Ayden; Cubillos, Paola; Werb, Dan; Milloy, M.-J.; Bonato, Sarah; Maghsoudi, Nazlee; Rueda, Sergio
Abstract: Background: We were engaged by policy stakeholders to undertake a scoping review of cannabis measurement instruments to inform the evaluation of cannabis legalization impacts. We identified instruments employed in population-based or clinical research to screen and assess cannabis use, including measurement properties. We also identified the content domains included in each instrument and gaps in the measurement of key priority areas as established by policy stakeholders. Methods: We followed PRISMA and conducted searches on MEDLINE, PsycINFO, Web of Science, EMBASE, HAPI, Scopus and grey literature. We included publications from the past 15 years that reported the use of an instrument to measure cannabis use. Six study team members calibrated screening and data abstraction, independently identified records and abstracted data. Results: Across 915 included publications, we identified 187 unique instruments covering seven content domains and 35 subdomains. The most identified instruments were the Composite International Diagnostic Interview, the Timeline Follow-Back and the National Epidemiologic Survey on Alcohol and Related Conditions (109/915; 91/915; 64/915). The Canadian Cannabis Survey addressed the most subdomains (22/35). Frequency of use, prevalence of use, and mental health impacts were the most addressed subdomains (110/187; 94/187; 67/187) and storage, growing cannabis, and second-hand exposure were the least addressed (1/187; 4/187; 6/187). Conclusion: This research identified instruments and domains critical to the assessment of public health impacts of cannabis legalization, which can facilitate the harmonization of measures to inform policy development. Future research should develop new instruments for less commonly-addressed constructs and thoroughly explore psychometric properties of existing instruments. Highlights: Measurement of the public health implications following cannabis legalization. Identifies instruments critical to the assessment of cannabis legalization impacts. Highlights less commonly addressed content domains on instruments for cannabis use. May facilitate harmonization of measures to inform policy development. Preliminary exploration of psychometric properties of identified instruments.